Analisis Isi Dalam Film Imperfect Terhadap Kepercayaan Diri - Arfian Suryasuciramadhan; Cindy Nurlaila; Lika Mulki Latief; Ninda Ela Putri; Qurrotul Aini (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Movies can be used as a means of sending messages, for example in the form of moral messages contained in a movie. Moral message contained in a movie the definition of morals in the dictionary is the good and bad of a person's actions and behavior. This research is intended to explain how women's self-confidence in the movie Imperfect. This research also aims to find out the reality, representation and ideology of women's self-confidence contained in the film's storyline that can be implemented in everyday life which discusses how women's self-confidence in appearance. The design in this research uses the Semantic Analysis method of Charles Sanders Pierce by taking the constructivism paradigm to see the moral message in moral message in the movie Imperfect. The results of this study explain that there are several body shaming behavior, namely looking at the physical, mockery and ridicule and the positive side is the existence of self-esteem in religious tolerance. positive side is the existence of self-esteem in religious tolerance, attention and self-confidence. The conclusion shows that body shaming behavior can make those who are bullied make those who are bullied so insecure that it is very disturbing mentally, while the nature of every body shaming is that it is mentally, while in essence every human being needs to get self-esteem from respect for themselves, others, and others. self-esteem from respect for himself, others, as well as the environment and life.